Decreasing Level Of Total Suspanded Solid (TSS) And Nitrate In Alcohol Traditional Wastewater Using Multi Soil Layering Electrolysis (MSLE) Method - Mahardika, Nanda Pratiwi; Fatimah, Siti (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2021)
Home industry for making alcohol traditional in Bekonang Village, Sukoharjo produces large volumes of liquid waste which is discharged into the river without going through any waste treatment. One of the wastewater treatment methods is Multi Soil Layering Electrolysis (MSLE) which is a combination of Multi Soil Layering (MSL) and Electrolysis methods used to reduce levels of Total Suspanded Solid (TSS) and Nitrate in Alcohol waste. The purpose of this experiment was to determine the effect of time and voltage variations and the effectiveness of using the Multi Soil Layering Electrolysis (MSLE) method to reduce traditional alcohol waste. The results showed that MSLE method is quite effective to reduce Nitrate levels by 82.06% with an effective voltage of 10 volts in 40 minutes. Meanwhile, for TSS levels increase until 164 mg/L with the voltage is 10 volts in 30 minutes.